Nilai-nilai Moral yang Terkandung dalam Tasawuf Al-Ghazali dan Pengaruhnya terhadap Etika Islam - Widyastini, Widyastini (Jurnal Filsafat "WISDOM", 2000)
This research aim is to know how far is the value of moral still being used by means of measurement in case of achieving human life happiness, especially in connection with God, human to human, and human to sicrumstances.When human without any bases on moral values, so the life of human will run imbalancely and more focus on his own needs than those society in general this case is based of princple; "Goals to permit all the ways" and the result is that human will be not human.For more knowing about and aknowledge more in deep about the probelm of moral, in which always scope human life, so it possibly need to observe and research moral value consisted in the tasawuf Al-Ghazali and the influence towards Islamic ethics, so that eventually, will be attained the benefits for Indonesian nations in which most people embrace Islamic religion, especially in running recent development.This research was held by having observed bibliographical studies, especially concerning with the title of the research, beth in the form of books and literatures by striving to look for data of tasawuf Al-Ghazali and the influence towards Islamic ethics.Based on the research results having been analized, so that it can be drawn some conclusion that in Islamic principles, the probelms of moral values discrussing about many probelms both of the good and bad become the most essential probelm, both the tasawuf Al-Ghazali and Islamic ethics and the influence of tasawuf Al-Ghazali towards Islamic ethics looked at and involved in the moral resource underlaying that is Al Qur'an and Al-Hadits.